(untitled) (The International Journal for Scientific Research, 2025)
Introduction: Oral and pharyngeal cancers pose a significant threat to human health, with approximately 12,000 cases reported each year in the United Kingdom. The development of these cancers is influenced by several risk factors, including human papillomaviruses (HPV types 16 and 32), tobacco use, alcohol consumption and in some cases vaping. Although earlier studies have shown an increasing incidence of oral cancer, there are still gaps in public knowledge about its symptoms and risk factors. Method: This study aimed to assess the knowledge of Arabic speaking population in the UK concerning oral and pharyngeal cancer. A structured questionnaire in Arabic was distributed via Google E.forms to 300 randomly selected participants. Data collection and analysis were conducted using SAS and Excel, following the ethical guidelines set forth by the Helsinki Commission (2013) Results: The findings obtained from the questionnaire show that a total of 300 participants contributed opinions regarding various risk factors that cause unhealthy habits. Among them, 60% admitted having smoked, while 18% confirmed consuming chewing tobacco and/or qat. Furthermore, 53% talked of smoking hookah, showing the rising tendency for taking on these behaviors that may correlate to the development of different Oral and pharyngeal cancer The data show that smoking poses the highest risk potential for Oral and pharyngeal cancer, irrespective of the type, tobacco, or hookah. Awareness campaigns targeting the symptoms and risks of these habits have indeed started to increase understanding and education in Arabic-speaking communities Conclusion: The incidence of oral and pharyngeal cancer is found to be possibly related to people’s ignorance about oral and pharyngeal cancer in general. Information among participating people, though different, may be limited and differ from one community to another.